Saúde e segurança do trabalho nas atividades laborais dos servidores técnico-administrativos da clínica obstétrica de um hospital universitário - Ramos, Hermano Albuquerque (2018)
Occupational health and safety in the hospital environment considers the measures and actions that can prevent and/or eliminate physical hazards, chemical, biological, ergonomic and accidents that can produce harms to health of the worker and the worker. The regulatory norms of the Ministry of labor and employment regulate this issue in Brazil, both in the private sector as public. The general objective of this research was to describe the aspects of safety at work and health of technical-administrative servers (TAE) in the work environment at the University Hospital Lauro Wanderley – HULW, in relation to occupational illnesses occurring in the last 5 years (2012 to 2016). The methodology of exploratory-descriptive nature, with PN approach, included case study, with field research and semi-structured questionnaire for data collection. The target audience were technical and administrative servers full in Obstetric Clinic of HULW (doctors, nurses and technicians. The data collected have been consolidated and analyzed by descriptive statistics and correlation using the R software version 3.3.2. The obtained results demonstrated that the TAE have knowledge about occupational diseases, work exposed the aggressive agents and, in most cases, apply correctly the measures prevencionistas. Most TAE understands and makes use of regulatory norms. However, the inconsistencies found lead to the conclusion that there is a need to create a policy of occupational health and safety in Obstetrical Clinic of HULW, directed to the control and prevention of diseases and infections, with an emphasis on actions and implementation of measures of protection in the working environment, as the regulatory norms of the Ministry of Labour (NR-15 and NR-32). These analyses are being passed on to the management and it is expected that actions can be implemented so that an environment conducive to the development of the preventive organizational culture can provide better working conditions and, as a result, best functional activity, satisfaction and productivity, improving the quality of life of health professionals and the occupational environment.